Overcoming the delivery problem for therapeutic genome editing: Current status and perspective of non-viral methods - Mashel T. V. Tatiana Vladimirovna; Tarakanchikova Ya. V. Yana Vladimirovna; Muslimov A. R. Albert Radikovich; Zyuzin M. V. Mikhail; Timin A. S. Aleksandr Sergeevich; Lepik K. V.; Fehse B. (2020, 2020)
Title screen